REPRESENTASI TRAUMA COPING DALAM DRAMA KOREA HOMETOWN CHA-CHA-CHA - Fristiani, Annisa Nadira; Abdullah, Aceng; Rosfiantika, Evi (Sintesa, 2024)
Trauma is an experience that has been experienced or felt by almost all individuals. Prolonged trauma then encourages the emergence of a trauma coping phase, which is the process of recovering an individual from a trauma. The number of traumatic experiences encourages drama films to raise the issue of trauma coping, one of which is the drama series Hometown Cha-Cha-Cha. This film first aired on the Total Variety Network and received great attention about trauma coping, resulting in 347,000 search results on the Google search engine since 2022. This research tells the story of the protagonist Hong-Du Sik, who is trying to confront his trauma after being in a relationship with Yoon Hye-Jin. However, the trauma-coping process carried out by the main character becomes complex because trauma coping is closely related to self-concept, relationships and interpersonal perceptions, which will be influenced by perception, memory and thinking. The more negative the self-concept, relationships and interpersonal perceptions, the less easy the trauma-coping process will be. Through a qualitative approach and the semiotic method of Charles Sanders Pierce, the researcher intends to look at the representation of trauma in the drama series. Through this research, it was found that the drama Hometowan Cha-Cha-Cha focuses on the traumatic experience of Hong Du-Sik, who has lost his family, forming a negative self-concept, which causes him to have difficulty establishing new relationships with others. After meeting Yoon Hye-Jin, Hong Du-Sik exhibits trauma coping strategies: confrontation, isolation, and compromise. The character's trauma coping strategies are visualised through clothing, verbal dialogue, actions and facial expressions. Not only that, this film also represents trauma coping that occurs in South Korea, which has experienced trauma, so this film really describes the actual situation.. keyword: representation; semiotic; film; trauma coping